Comparative analysis of aroma compounds in French fries and palm oil at three crucial stages by GC/MS‐olfactometry, odor activity values, and aroma recombination. (2nd December 2021) - Xu, Lirong; Chang, Jiarui; Mei, Xue; Zhang, Youfeng; Wu, Gangcheng; Jin, Qingzhe; Wang, Xingguo
Abstract: BACKGROUND: Flavor is a key element affecting the popularity of French fries (FFs). When oil is heated, the changes in oil quality can affect the flavor of the food directly. RESULTS: The flavor of FFs showed three crucial stages: the break‐in (3.0% to 6.8% of total polar compounds (TPC)), optimum (7.0% to 19% of TPC), and degrading (above 19.5% of TPC) stages. To distinguish the key aroma compounds in the three stages, the FFs, prepared in palm oil (PO) at TPC of 3.0% (FF3), 7.5% (FF8), 19.5% (FF20), and their relevant oils (PO3, PO8, PO20), were selected for molecular sensory science analysis. The results indicated that the concentration of (E, E)‐2, 4‐decadienal linked with the deep‐fried odor was low in FF3, which led to a lower sensory score in the FF3 sample. The FF8 sample had a high (E, E)‐2, 4‐decadienal content and received a high sensory score. The FF20 sample possessed high hexanoic acid, heptanoic acid (sweaty odor), benzaldehyde (stale odor), octanoic acid (sweaty odor), (E)‐2‐undecenal (fatty odor), and trans ‐4, 5‐epoxy‐(E)‐2‐decenal (metallic odor) content, thus leading to FFs having an undesirable flavor and PO20 showed high hexanoic acid and heptanoic acid content, contributing to a lower sensory score in PO20. CONCLUSION: The FFs' flavor became undesirable when TPC was above 19.5% due to significant influences of some off‐flavor compounds. It is therefore essential to prevent the generation of rancid substances to prolong the optimum stage during frying. © 2021 Society of Chemical Industry.